The consequences of seasonal fasting during the dormancy of tegu lizards (Salvator merianae) on their postprandial metabolic response - Gavira, Rodrigo S. B. [UNESP]; Sartori, Marina R. [UNESP]; Gontero-Fourcade, Manuel N.; Gomes, Bruna F. [UNESP]; Abe, Augusto S. [UNESP]; Andrade, Denis V. [UNESP] (Company Biologists Ltd, 2018)
Tegu lizards (Salvator merianae) aestivate for up to 5 months during Brazil's winter, when they retreat to burrows and halt most activities. Dormant tegus reduce their gastrointestinal (GI) mass, which allows a substantial energy economy. This strategy, however, implies that the first post-dormancy digestion would be more costly than subsequent feeding episodes as a result of GI atrophy. To address this, we determined the postprandial metabolic response (SDA) of the first (M1), second (M2) and several (RM) feeding episodes after tegus' dormancy. Another group of tegus (PF) was subjected to an extra 50 day fasting period after arousal. Glucose, triglycerides and uric acid levels were checked before and after feeding. M1 digestion lasted twice as long and cost twofold more when compared with M2 or RM, in agreement with the idea that GI atrophy inflates digestion cost at the first post-dormancy meal. The SDA response was similar in M2 and RM, suggesting that the GI tract was fully reorganized after the first feeding. The SDA cost was equal in PF and RM, implying that the change in state per se (dormant to arousal) triggers the regrowth of GI, independently of feeding. Fasting tegus at M1 presented higher triglyceride and lower uric acid levels than fed tegus, indicating that fasting is mainly sustained by fat storage. Our results show that seasonal fasting imposes an extra digestion cost to tegus following their next feeding, which is fully paid during their first digestion. This surplus cost, however, is negligible compared with the overall energetic savings from GI tract atrophy during the dormancy period.
Keywords: Metabolism; Dormancy effects; Gastrointestinal tract; Atrophy; Specific dynamic action; Blood metabolites